Initial testing (stage 1) of BAL101553, a novel tubulin binding agent, by the pediatric preclinical testing program. Issue 6 (18th November 2014) - Kolb, E. Anders; Gorlick, Richard; Keir, Stephen T.; Maris, John M.; Kang, Min H.; Reynolds, C. Patrick; Lock, Richard B.; Carol, Hernan; Wu, Jianrong; Kurmasheva, Raushan T.; Houghton, Peter J.; Smith, Malcolm A.
<x xml:space="preserve">Abstract</x> BAL101553 is a highly water soluble prodrug of BAL27862 that arrests tumor cell proliferation and induces cell death in cancer cells through disruption of the microtubule network. In vitro BAL27862 demonstrated potent activity, with the median relative IC50 (rIC50) of 13.8 nM (range 5.4–25.2 nM). The in vitro activity of BAL27862 against the PPTP cell lines is distinctive from that previously described for vincristine. BAL101553 induced significant differences in EFS distribution compared to control in 16 of 30 (53%) solid tumor xenografts and in two of four (67%) of the evaluable ALL xenografts. No objective responses were observed. Pediatr Blood Cancer 2015;62:1106–1109. © 2014 Wiley Periodicals, Inc.